2019
DOI: 10.1096/fj.201802512rr
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A‐l improves pancreatic β‐cell function independent of the ATP‐binding cassette transporters ABCA1 and ABCG1

Abstract: Apolipoprotein A‐I (apoA‐I), the main protein constituent of HDLs, increases insulin synthesis and insulin secretion in pancreatic β cells. ApoA‐I also accepts cholesterol that effluxes from cells expressing ATP‐binding cassette transporter A1 (ABCA1) and ATP‐binding cassette transporter G1 (ABCG1). Mice with conditional deletion of ABCA1 and ABCG1 in β cells [β‐double knockout (DKO) mice] have increased islet cholesterol levels and reduced glucose‐stimulated insulin secretion (GSIS). The project asks whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
4
16
0
Order By: Relevance
“…HDL has further been suggested to influence pancreatic β-cell function and survival ( Figure 2 , right part). The deletion of either ABCA1 or ABCG1 in β-cells in mice have resulted in increased intracellular cholesterol levels and thus impaired insulin secretion [ 117 , 118 , 119 ]. Robust evidence from the general population has not confirmed that these findings in mice translate into increased risk of type II diabetes in humans [ 120 ].…”
Section: Diabetesmentioning
confidence: 99%
“…HDL has further been suggested to influence pancreatic β-cell function and survival ( Figure 2 , right part). The deletion of either ABCA1 or ABCG1 in β-cells in mice have resulted in increased intracellular cholesterol levels and thus impaired insulin secretion [ 117 , 118 , 119 ]. Robust evidence from the general population has not confirmed that these findings in mice translate into increased risk of type II diabetes in humans [ 120 ].…”
Section: Diabetesmentioning
confidence: 99%
“…However, the precise mechanism by which apoA-I improves β-cell function in this animal model has yet to be elucidated. What we do know is that the observed benefit is not related to the restoration of β-cell cholesterol homeostasis in the case of mice with conditional deletion of ABCA1 and ABCG1 in β-cells [24]. Nor is it related to improved glucose metabolism or to the inhibition of inflammation [24].…”
Section: Apolipoprotein A-i and Apolipoprotein A-iimentioning
confidence: 98%
“…Evidence that the antidiabetic functions of apoA-I and apoA-II translate into improved glycaemic control in vivo is mounting. For example, lipid-free apoA-I treatment increases glucose-stimulated insulin secretion (GSIS) in C57BL6 mice with diet-induced obesity, and in isolated islets from mice with elevated islet cholesterol levels and impaired insulin secretion due to the conditional deletion of the ATP binding cassette transporters, ABCA1 and ABCG1, which export cholesterol from β-cells to lipid-free/lipid-poor apoA-I and HDLs, respectively [24,26,27,79]. However, the precise mechanism by which apoA-I improves β-cell function in this animal model has yet to be elucidated.…”
Section: Apolipoprotein A-i and Apolipoprotein A-iimentioning
confidence: 99%
See 1 more Smart Citation
“…ATP-binding cassette transporter A1 (ABCA1) is a member of the ATP-binding cassette transporter family which binds and hydrolyzes ATP, using the energy generated to transport substances including lipids, sterols, and cell metabolites. [6][7][8] ABCA1 was previously shown to play a key role in the reverse transport of cholesterol. 9 Recent studies have shown that ABCA1 is essential for normal glucose regulation, such as on islet b cells.…”
Section: Introductionmentioning
confidence: 99%